The ecological functions of Asian elephants in the Sundaic rainforest: herbivory and seed dispersal - Ong, Lisa (2021)
Asian elephants (Elephas maximus) are among the last remaining megaherbivores in the Sundaic rainforests. In this thesis, I aimed to improve our understanding of the ecological roles of rainforest-dwelling Asian elephants through their herbivory and seed dispersal behaviours. A comprehensive review in Chapter One revealed that there have been few investigations of their interactions with the community and the habitats they live in. In Chapter Two, I advanced our understanding of Asian elephants in modifying the rainforest structure by quantifying their diet selection and herbivory impacts. The principal foods of Asian elephants in rainforests were palms (39% of total trunkfuls consumed) and trees (30%). They preferred monocots, particularly palms (preference ratio=4.6; below 1=avoidance) that are not abundant in the forest, and most monocots sustained high damage due to elephant foraging (above 40% in foraged patches). Their feeding behaviour was associated with a reduced palm density in the Royal Belum rainforest where elephants roam, as compared to a forest lacking elephants in Krau Wildlife Reserve. Although large tree saplings (around 21 cm diameter) were vulnerable to elephant damage, they had high recovery rates, and elephant herbivory is likely not the sole factor causing lower tree sapling density in Belum. Asian elephants are important seed dispersers. In Chapter Three, I recorded rare interactions of Asian elephants and a large-fruited rainforest tree, Irvingia malayana (Irvingiaceae) through the use of camera-traps. The removal rate of fruits by elephants was low, yet seed dispersal by elephants allowed Irvingia malayana seeds to escape from high levels of seed predation by wild boars. In Chapter Four, using network analysis, I identify Asian elephants as dominant functional generalists promoting seed dispersal diversity within the community. This is the first highly diverse seed dispersal network in the Sundaic region, built using an inter-disciplinary approach, which combines ethnobotany knowledge, feeding signs on fruits, camera-trapping, and published literature. Elephants had high species strength and were important to both the dispersal of plants central to the network and the dispersal of large-fruited species. Along with other important seed dispersers such as gibbons (the most efficient seed dispersers), binturong, civets, and the Malayan sun bear, they promoted network nestedness and functional redundancy. Simulation of defaunation of important, highly-connected seed dispersers caused adverse co-extinctions of seed dispersal interactions. Urgent protection of important and vulnerable rainforest species is needed in the Sundaic region. This thesis confirms the importance of Asian elephants as selective feeders for palms and tree saplings. It describes their interactions with tropical Sundaic fruits and confirms Asian elephants as functionally dominant seed dispersers within the seed dispersal community.